Analysis of Sand Mineral Health Status in Batang Kuranji River Kota Padang Th 2018 - ., Mahaza; ., Awaluddin (KnE Life Sciences, 2019)
According to Hendrik L, there are four factors that affect the health status of the public and individual. These factors can be described as follows: (1) Environment, (2) Behavior, (3) Health services, and (4) Descendants. Rivers usually are the main source of water for residents’ daily needs such as bathing and washing. Batang Kuranji has been a source of livelihood for the community for decades, such as mining sand, stone, and gravel as materials for development. From the initial survey that the author did on three sand miners, it turned out that two of them were 55 years old, have five children, of which three are toddlers; another person is a 16-year-old teenager who does not continue school anymore and has only completed elementary school (SD). This determination aims to describe the health status of the sand miners of the Batang Kuranji River in Padang City. The results of the study showed that the condition of the environmental health of the sand fishermen was still poor because 75% of the sand miners did not have sanitary toilets, and 80% did not have a proper understanding of personal hygiene. So, 95% of sand miners smoke in their homes, 75% like to stay up late. Health Service Factors Ownership of BPJS cards and health counseling Ownership of BPJS cards: 55% of the miners did not have BPJS and 62% of the cardholders have never received health counseling from health workers. Heredity/Heredity factor of 35% has been the second generation and 10% of the third generation has worked in sand mining. As a suggestion for Puskesmas Parties to further improve the health service programs, health agencies provide guidance programs to government officials such as RT/RW to pay more attention to the sand mining community by providing and involving these community groups in improving improve their health status such as livestock and other businesses to support the family economy. Further research needs to be done on more complete variable health variables.